Growth of Democratisation in Latin America Along Socialist Lines - Mishra, Amit (Jurnal Ilmiah Hubungan Internasional, 2012)
Latin America is a highly volatile region. After it was exposed to the rigours of colonialism, it has experienced several doses of authoritarian rule before the process of democratisation gained momentum in the 1980s. This article analyses the tenor and quality of democratisation along socialist lines in three countries of Latin America. The paper tries to identify the positive aspects of socialist democracies in the volatile but resource-rich region and at the same time clearly highlights the shortcomings in the socialist experiments in Brazil, Chile and Urugay. All these countries are able to achieve the social democratic goal of high rates of economic growth while at the same time ensuring social justice. In all the three cases poverty fell significantly and income inequality also decreased. However the author also highlights that these neo-leftist regimes have been often repressive towards minority voices leading to a sense of alienation among a significant section of their population.Keywords : Latin America, socialist democrazy, Brazil, Uruguay, Chile, Democratisation, poverty alleviation, minority voices, authoritarism, repression, populist